New integral functions generated by rising factorial powers - Goy, T.P.; Zatorsky, R.A. (Carpathian Mathematical Publications, 2013)
We consider new nonelementary functions such as the Fresnel integrals, generated by rising factorial powers. Graphs of such functions are plotted and some of their properties are proved. It is shown, that new integral functions are solutions of second order ordinary differential equations with variable coefficients.